Investigating factors of online payment technology in influencing consumer purchase behavior - Chua, Jun Quan (2024)
The rapid advancement of technology has changed and impacted people's ways of living. In light of the increasingly technologically advanced and networked society, it is critical to comprehend the variables impacting how the consumer behaves when it comes to online payment technologies. In this case, this research project aims to investigate the factors of online payment technology in influencing consumer purchase behavior in terms of perceived trustworthiness, privacy, and security concerns, perceived usefulness, and user experience design of the online payment technology. To ensure the reliability of the research, a total of 400 respondents were collected through convenience sampling methods. The survey questionnaire is designed based on the perspective of perceived trustworthiness, privacy and security concerns, perceived usefulness, and user experience design of online payment technology, which is also sent to the respondents by using social media platforms. After all, Microsoft Excel and SPSS were utilized to perform the data analysis based on the responses from the respondents. Additionally, the findings of the result indicated that all of the independent variables (Perceived Trustworthiness, Privacy, and Security Concerns, Perceived Usefulness, and User Experience Design) significantly predict consumer purchase behavior. As such, the present results of the study also provided additional insights for future researchers and policymakers in developing possible relationships between the independent variables and possible changes in consumer purchase behavior.